OBSERVASI POPULASI SERANGGA PENYERBUK KELAPA SAWIT (Elaeidobius kamerunicus Faust) PADA KETINGGIAN TEMPAT YANG BERBEDA - Muhammad Arif Fakhri Simarmata; Hari Gunawan (JURNAL AGRICA, 2026)
This study aimed to determine the population of the pollinator insect Elaeidobius kamerunicus Faust at different altitudes, the factors influencing it, and its relationship to oil palm fruit set. The study was conducted at two locations with different altitudes: 12 meters above sea level (Tanah Itam Ulu Plantation) and 715 meters above sea level (Bah Birung Ulu Plantation), from September to November 2025. The method used was descriptive quantitative, with primary data collected through direct observation of the insect population on anthesis male flowers, and secondary data collected from weather factors (temperature, humidity, and rainfall). The results showed that the population of E. kamerunicus per hectare was higher at 12 meters above sea level, at 119,262 individuals/ha, compared to 70,692 individuals/ha at 715 meters above sea level. This difference was influenced by environmental factors such as temperature, humidity, and rainfall, as well as biotic factors such as the number of male flowers blooming and the number of spikelets per bunch. Environmental conditions at lower elevations, with higher temperatures (31°C), lower humidity (79%), and lower rainfall, favor the activity and development of pollinating insect populations. Conversely, at higher elevations, with lower temperatures (22.1°C), high humidity (85%), and high rainfall, insect activity tends to be inhibited. Fruit set rates also showed a difference, reaching 87% at 12 meters above sea level and 79% at 715 meters above sea level. This indicates that the E. kamerunicus population influences the success of pollination and fruit set in oil palms. The higher the pollinating insect population, the higher the fruit set rate.